The Use of Information Technology in The Tarbiyah Department of The Faculty of Islamic Studies, Muhammadiyah University of Malang - Apriyal Fakih (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to describe the reasons why the Tarbiyah Department emphasizes competence in the field of Information Technology (IT) for its students and to explain the efforts made by the department to provide such competence. This research uses a qualitative approach, with the subjects consisting of the Dean of the Faculty of Islamic Studies (FAI) at Muhammadiyah University of Malang (UMM) for the 2005–2009 period, Drs. Khozin, M.Si; the Vice Dean I of FAI UMM for the 2005–2009 period, Drs. Sunarto, M.Ag; the Head of the Tarbiyah Department, Dra. Romlah, M.Ag; and the lecturer of IT-based courses in the Tarbiyah Department, Ir. Wahono, MT. The Tarbiyah Department of FAI UMM was chosen as the research setting based on field findings. First, among 29 students taking the Educational Technology course in the sixth semester of the 2008–2009 academic year, only five achieved a “very good” score. Second, there was a “contradictory implementation” in which two of four students who had completed their teaching practicum (PPL) at a multimedia-based school—Madrasah Aliyah Negeri III Malang, Jalan Bandung—did not apply several materials previously taught, particularly those from the Educational Technology course. Third, 65% of 28 students who had completed the Educational Information System Planning course in the odd semester of the 2007–2008 academic year were unable to re-operate (had forgotten) the material taught. Data collection techniques included participatory observation, interviews, and documentation. Data analysis was conducted using a qualitative data analysis model. The results of the study show that there are two main reasons why the Tarbiyah Department of FAI UMM emphasizes competence in IT: (1) to support the professional competence of Tarbiyah students in their respective fields, and (2) to serve as a distinctive advantage of graduates from the Tarbiyah Department of the Islamic Education Study Program at FAI UMM, differentiating them from graduates of other Islamic Education Study Programs. Efforts to provide IT competence are carried out through two processes: (1) curriculum design and development, and (2) teaching and practicum in IT-based courses